Persepsi GMAHK Jemaat Tincep Minahasa Terhadap Mati Adalah Tidur Berdasarkan Yohanes 11:11,13 - jeki momuat; Bartholomeus Diaz Nainggolan; Stimson Hutagalung; Dwi Andrianta (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
The events of death that God allows make very deep sorrow, even frustration and despair in life. This is triggered by ignorance about the real condition of the dead. From this background, the purpose of this study is to explore the knowledge of the congregation about the condition of the dead based on John 11:11 and 13, after which the data obtained will be analyzed and finally a final conclusion will be drawn. The research method used is a quantitative method with a survey approach. The data collection technique was using a questionnaire and distributing it to the members of the Minahasa Congregation of Minahasa GMAHK congregation. The number of samples used is 70% of the adult members totaling 119 people, then the sample taken is 83 people. The results of the questionnaire were used to analyze the understanding of church members about death as sleep. The result of this research is that the Tincep Minahasa congregation has an understanding that people who die are like sleeping people and will rise again when Jesus comes the second time, not an understanding that the dead have spiritual life in another world.